Osteoarticular and soft-tissue melioidosis in Malaysia: clinical characteristics and molecular typing of the causative agent - Zueter, AbdelRahman Mohammad; Abumarzouq, Mahmoud; Yusof, Mohd Imran; Wan Ismail, Wan Faisham; Harun, Azian (The Journal of Infection in Developing Countries, 2017)
Introduction: Melioidosis involving bone, joints, and soft tissue is rare and reported usually following dissemination of disease from infection elsewhere in the body; to a lesser degree, it can also be reported as the primary manifestation of melioidosis. Methodology: The orthopedic registry at Hospital University Sains Malaysia from 2008 until 2014 was retrospectively reviewed and was followed by molecular typing of Burkholderia pseudomallei. Results: Out of 20 cases identified, 19 patients were confirmed to have osteoarticular and/or soft-tissue melioidosis. The majority of the patients were males (84%), and 16 patients had underlying diabetes mellitus with no significant estimated risk with the disease outcomes. Bacterial genotype was not associated with the disease as a risk. Death was a significant outcome in patients with bacteremic infections (p = 0.044). Conclusion: Patients with lung or skin melioidosis require careful treatment follow-up to minimize the chance for secondary osteoarticular infection. Human risk factors remain the leading predisposing factors for melioidosis. Early laboratory and clinical diagnosis and acute-phase treatment can decrease morbidity and mortality.